Insurance management in Africa - Irukwu, J. O. (Ibadan, Nigeria : The Caxton Press, 1977)
In this new book, the author is conscious of the lack of adequate literature on insurance management in Africa. So, in the light of realities existing in his own country, he has committed to paper many valuable thoughts and suggestions, one of which is his keen analytical methodology in this book which delves deep into the heart of the problem, casting aside the irrelevant and retaining only what is basic and fundamental.
Includes index.
Includes bibliographical references: p. 421-422.
II 15/01/2019
Loans
Keywords: Insurance; Insurance companies